(x - 4y)(x+4y)+6xy

(x-4y)(x+4y)+6xy =x^2+6xy-16y^2 =(x-2y)(x+8y)


6xy[x^2(5x+3) - 3x^2( - 4y)]

½â£º6xy[x^2(5x+3)-3x^2(-4y)]=6xy[x²(5x+3)-3x²(-4y)]=6xy*x²[5x+3+12y]=6x³y(5x+12y+3)...


x+4y+6xy=2?

Êýѧ x+4y+6xy=2? ¹Ø×¢Õß1 ±»ä¯ÀÀ3 ¹Ø×¢ÎÊÌâд»Ø´ð ÑûÇë»Ø´ð Ìí¼ÓÆÀÂÛ ·ÖÏí ÔÝʱ»¹Ã»Óлشð,¿ªÊ¼Ð´µÚÒ»¸ö»Ø´ð...


...ÈçÏÂ:x¡ùy=5x+4y,x¡ðy=6xy.Çó(3¡ù4)¡ð5µÄÖµ.

½â´ð:½â:(3¡ù4)¡ð5,=(5¡Á3+4¡Á4)¡ð5,=31¡ð5,=6¡Á31¡Á5,=930.


Ò»µÀÊýѧÌâ,ÇóÖ¤:7x² - 6xy+4y²=1990ÎÞÕûÊý½â...

ÒòΪ-6xy,4y,1990ÊÇżÊý,ËùÒÔ7xÊÇżÊý,ËùÒÔxÊÇżÊý,ËùÒÔ4|7x,4|4y,4|-6xyËùÒÔ4|1990.ì¶Ü.ËùÒÔ7x-6xy+4y=1990ÎÞÕûÊý½â. ½âÎö¿´²»¶®?Ãâ·Ñ²é¿´Í¬ÀàÌâ...


2.5x*4y¡ª6xy»¹Äܼò»¯Âð

£¨3¡ù4£©¡ð5£¬=£¨5¡Á3+4¡Á4£©¡ð5£¬=31¡ð5£¬=6¡Á31¡Á5£¬=930£®


6xy+4y - 3x - 2 ·Ö½âÒòʽ

½â£º6xy+4y-3x-2 £½2y©v3x£«2©w£­©v3x£«2©w£½©v3x£«2©w©v2y£­1©w.


6xy=24. Çó½â

6xy=24 xy = 4 y = 4/x ´ËÌâ¶à½â¡£²¿·Ö½âÈçÏ£ºx y 1 4 2 2 3 1.333333333 4 1 5 0.8 6 0.666666667 7 0.571428571 8 ...


¼ºÖªx+4y= - 1,xy=5,Çó(6xy+7y)+ [8x - (5xy - y+6x)]µÄÖµ...

3


...A. 3x+3y=6xyB. 7x - 5x=2C. 4a2+a3=5a5D. 6xy2 - 4y...

½â´ð:½â:A¡¢3xÓë3y²»ÊÇͬÀàÏî,²»Äܺϲ¢.´íÎó;B¡¢7x-5x=2x.´íÎó;C¡¢4a2Óëa3²»ÊÇͬÀàÏî,²»Äܺϲ¢.´íÎó;D¡¢6xy2-4y2x=2xy2.ÕýÈ·.¹ÊÑ¡D.


Ïà¹ØËÑË÷

ÈÈÃÅËÑË÷